Pengaruh Senam Diabetes Terhadap Penurunan Kadar Gula Darah Pasien Diabetes Mellitus di Puskesmas Bah Kapul Pematangsiantar Tahun 2019 - Romauli Pakpahan; Marlon Sijabat (Communication and Social Dinamics (CSD), 2020)
This study aims to determine the effect of diabetes gymnastics on the decrease in blood sugar levels of diabetic patients at the puskesmas Bah Kapul Pematangsiantar. This research was conducted in Juni - Agustus 2017, the design of this study was comparative. The sample size in this study were 21 respondents obtained by total population sampling. Data were obtained through questionnaires, interviews and direct capillary blood sampling of respondents to then measured blood sugar levels by using glucose meter. Data analysis was done gradually including descriptive and paired samples t-test. The results of this study showed that before doing gymnastics in the first week of the average blood sugar levels of respondents was 272.4 mg / dl and after doing gymnastics in the fourth week of the average blood sugar levels of respondents was 257.04 mg / dl, blood sugar of 15.36 mg / dl. Result of paired samples t-test significantly decrease blood sugar level at respondent with p value of 0,041. This means that there is influence of diabetes gymnastics to the decrease of blood sugar level of diabetic patient. It is expected for health service to be a motivator and provide intensive counseling for people with diabetes mellitus to do gymnastic gymnastics routine to lower blood sugar level and prevent complication of diabetes mellitus. Keywords: gymnastics diabetes; blood sugar